Exploring Contemporary Intellectual Approaches to the Sirah Nabawiyyah: A Comparative Analysis of Modern Islamic Historiography - Muhammad Riedho; Saiful Umam (Divisi Penelitian dan Pengabdian Masyarakat Yayasan Cerdas Pedia Indonesia, 2026)
Historiography in Islamic studies serves as a crucial epistemological framework for documenting the life of the Prophet Muhammad ﷺ, balancing textual authenticity and contemporary relevance. This research conducts a comparative analysis of two seminal modern works: ar-Rāḥīq al-Makhtūm by Ṣhafīurrahmān al-Mubārakfūrī and Fiqh Ṣīrah by Sa‘īd Ramadhān al-But̲h̲ī. It examines how Salafi-Hadith and Asy‘arī-Syāfi‘ī intellectual traditions shape narrative structure, source verification, and methodological orientation. The study highlights al-Mubārakfūrī’s commitment to chronological narration and stringent sanad-matan critique alongside al-But̲h̲ī’s thematic-integrative approach that extracts legal and ethical lessons from prophetic events. Findings reveal that ar-Rāḥīq prioritizes historical certainty through preservation of authentic reports, while Fiqh Ṣīrah emphasizes functional applicability by deriving jurisprudential and moral insights. The research concludes with methodological recommendations for synthesizing rigorous verification and contextual analysis, aiming to advance future Islamic historiography that is both authoritative and pragmatically transformative.